Responsabilidad patrimonial del Estado en Colombia por violación al derecho moral de paternidad - Flórez Acero, Germán Darío (Pontificia Universidad Católica del Perú, 2025)
This paper examines the responsibility of the Colombian State for violating moral rights in copyright, specifically the right of attribution when public officials commit plagiarism. It explains the distinction between moral and economic rights in Colombian law, focusing on the right of attribution as regulated by Law 23 of 1982 and Andean Decision 351 of 1993. The paper also explores the liability of public officials and relevant case law, along with a practical exercise on how to calculate damages for such infringements. This research is a product of the Private Law Research Group at the Universidad Sergio Arboleda.

Este trabajo analiza la responsabilidad del Estado colombiano por la violación del derecho moral de autor, específicamente el derecho de paternidad, cuando funcionarios públicos cometen plagio. Se explica la distinción entre derechos morales y patrimoniales en la legislación colombiana, con énfasis en el derecho de paternidad según la Ley 23 de 1982 y la Decisión Andina 351 de 1993. También se examina la responsabilidad de los funcionarios y la jurisprudencia relevante, además de un ejercicio práctico sobre el cálculo de los perjuicios ocasionados por estas infracciones. Este estudio es resultado del grupo de investigación en Derecho Privado de la Universidad Sergio Arboleda.
Patrimonial liability of the State in Colombia for violation of the moral right of attribution
Keywords: Copyright; Liability and intellectual property; Derecho de autor; Responsabilidad estatal; Propiedad intelectual; https://purl.org/pe-repo/ocde/ford#5.05.00